Health promotion activity in Kampung Tengah - Che Ismail Che Noh; Oberni Robert @Cliftrich; Dhanasrree Loganathan; Vincent Tio Chung; Adlin Liyana Johari; Noorin Ab Nasir; Sulaiman Sunil; Fatin Najieha Mohd Affindee; Nurul Hidayathulzakiyah; Michelle Clara Benjamin; Siti Rohani Asrakal; Pee, Vivien Vanessa Lee Xin; et al. (Universiti Malaysia Sabah, 2016)
Health Promotion is a collaborative program between medical and nursing students of Faculty of Medicine and Health Science (FMHS), u·niversity Malaysia Sabah. Group 8 consists of 13 group members; 9 first year medical students and 4 second year nursing students. The group was supervised by Dr. Che Ismail. Ten days of Health Promotion was conducted in Kampung Tengah, Bongawan starting from 24th August 2016 untill 200 September 2016. The presence of the students was well accepted henceforth provide a great help in maintaining the success of the program. During our stay, rapid rural appraisal was done to obtain the general overview about the village regarding their health status and to identify the cause of problems which may jeopardize the people's health. Therefore, solutions were taken in order to promote health in the village. Besides that, the group had organized many activities aiming to provide knowledge and increase awareness among the people as well as empowering them to take control of their own health and practice healthy living. All of the activities are as such: 1. Rapid Rural Appraisal (RRA) which includes the house-house visit, direct or field observation, key informant interview, individual interview, group meeting interview and discussion, health screening and also the social mapping. 2. Health education and health awareness by the means of organising medical checkup, health talk and exhibitions which involve participation from the villagers with various age groups. 3. Lifestyle and behavioural changes. For example, talk regarding hand washing and first aids. It is to promote proper hygiene and provide knowledge regarding simple bandaging technique and wound cleaning among students. 4. Sports activities. Aerobic exercises and Sports day in both school and Kampung Tengah respectively 5. Environmental modification by organizing focus group interview and discussion among elderly of the villagers to propose the best ways for the management of the waste in the village.